Hubungan Beban Kerja dan Budaya Organisasi serta Perceived Organizational Support terhadap Kinerja Karyawan PT Bank Pembangunan Daerah Bali (Jurnal Agribisnis dan Agrowisata, 2026)
The Relationship of Workload and Organizational Culture and Perceived Organizational Support on Employee Performance of PT Bank Pembangunan Daerah Bali. Human resources are crucial to the success of an organization. Effective management of human resources is the key to achieving organizational goals. PT Bank Pembangunan Daerah Bali (BPD Bali) is a company engaged in banking that requires employee performance to advance the company. The purpose of this study is to identify the relationship between workload and organizational culture and perceived organizational support on employee performance of PT BPD Bali. The sample of this study used proportional random sampling technique with a total of 72 people. Research data obtained from the results of a questionnaire with a questionnaire. This research was processed using Structural Equation Modeling (SEM) data analysis with the Smart PLS 4 program as the analysis tool. The results of this study indicate that workload has a negative and significant relationship to employee performance, which means that if workload increases, it will reduce the potential performance of employees and organizational culture and perceived organizational support have a positive and significant relationship to employee performance, meaning that the organizational culture and organizational support perceived by employees is good and strong, it will increase the potential of the performance of BPD Bali employees themselves. PT BPD Bali is advised to pay attention to the portion of employee workload, optimize organizational culture, and increase organizational support for employees.
Keywords: workload; organizational culture; perceived organizational support; employee performance; PT. BPD Bali